Immunogenicity and safety of SARS-CoV-2 vaccines in clinical trials - Lim, Hui Xuan *; Masita, Arip; Abdul Aziz, Al-Fattah Yahaya *; Jazayeri, S. D. *; Poppema, Sibrandes *; Poh, Chit Laa * (IMR Press, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections were first detected in Wuhan, China in December 2019 and resulted in a worldwide pandemic in 2020. SARS-CoV-2 infections totalled more than 180 million with 3.9 million deaths as of June 24, 2021. Tremendous research efforts have resulted in the development of at least 64 vaccine candidates that have reached Phase I to III clinical trials within 14 months. The primary efficacy endpoint for a random placebo-controlled clinical trial of a COVID-19 vaccine to be approved by US FDA should confer at least 50% protection against COVID-19. Three COVID-19 vaccines (BNT162b2, mRNA-1273 and Sputnik V) in clinical Phase III trials have now achieved >90% efficacy in preventing COVID-19. Since SARSCoV-2 is highly contagious, vaccines are expected to achieve at least 80% herd immunity in the world’s population to effectively prevent SARS-CoV-2 infections. An overview of safety, immunogenicity and efficacy of the current frontrunner vaccines are reviewed.